School Management in Preventing Bullying in Primary Schools - Maryati, Neneng Meri; Hidayat, Hidayat; Sulastri, Neneng; Anwar, Saeful (Papanda Publisher, 2025)
Bullying in primary schools poses significant threats to student well-being and academic achievement, requiring effective school management approaches for prevention. This study examined differences in bullying prevention management between rural and urban primary schools to understand how contextual factors influence implementation effectiveness. A qualitative comparative case study was conducted at two primary schools in Cianjur Regency, West Java: SD Negeri Kebonpeuteuy 2 (rural) and SD Negeri Sayang 2 (urban). Data collection employed triangulated methods including systematic observation, semi-structured interviews with twelve key informants, and document analysis. Thematic content analysis was applied using Deming's four-stage management cycle framework encompassing planning, implementation, monitoring, and follow-up phases. Rural schools demonstrated informal, culturally-embedded approaches emphasizing local wisdom integration (silih asah, silih asih, silih asuh), community-based supervision, and dialogical mediation for conflict resolution. Urban schools implemented systematic, technology-enhanced strategies featuring formal documentation, structured peer ambassador programs, digital monitoring systems, and professional external support. Both contexts showed effectiveness within their respective resource constraints and community characteristics, with rural schools leveraging social capital and urban schools utilizing formal organizational capacity. Findings reveal that effective bullying prevention management requires contextually responsive approaches rather than standardized procedures. Rural schools' cultural integration demonstrates community-embedded prevention strategies, while urban schools' systematic approaches reflect formal organizational readiness. The study contributes to educational management literature by extending organizational capacity theory and providing frameworks for adaptive prevention policies that integrate systematic implementation with culturally responsive strategies for sustainable bullying prevention across diverse educational contexts.